APPLICATION OF XYLOMETAZOLINE FOR CHEMO-MECHANICAL RETRACTION OF THE FREE GINGIVA. - Iveta Katreva; Kalina Georgieva; Simeon Simeonov; Maya Doychinova; Tsvetan Tonchev (Peytchinski Publishing, 2015)
To carry through a contemporary treatment plan in accordance to the functional, prophylactic and esthetic requirements in fixed prosthodontics the dental specialist needs highly precise impressions for perfect marginal fit of the constructions. An accurate impression of the marginal details of the preparations is the only way to successful restorations in prosthetic dentistry. Gingival retraction is a long established technique which allows access in preparation, guarantees ingress of impression material around the preparation shoulder into the gingival groove and facilitates cementation procedures.